Actor Constellation Games in Policy Implementation—The Case of Switzerland1. (6th January 2019) - Knoepfel, Peter
Abstract : This analytical essay deals with the policy resource organization which policy actors employ to influence policy implementation activities. We speak of games of actor constellations that potentially influence the content of policy implementation activities. In the last 50 years, the scope of these games has broadened due to their increasing complexity. Initially shaped as simple bilateral structures formed by policy targets and the state, these constellations have become trilateral, encompassing the policy beneficiaries and, subsequently, affected the third party groups as well as the supporting or opposing actors within the public administration. Based on imaginable and/or empirically existent cases, this contribution establishes thirteen types of actor constellation games which are presented with concrete examples.